Criteria and Factors for the Selection of a Registered Auditor - Lecheva, Ina (Research Papers, 2024)
Choosing a registered auditor to perform a statutory or voluntary financial audit is an important and difficult task for businesses. There are a number of criteria and factors that can influence the choice of a registered auditor – a natural person or an audit companies. The publication examines the results of a survey among managers and key managers of enterprises of different categories and sectors concerning their attitudes in the selection of an auditor.